THU0334 EFFECT OF THE DELAY FROM INITIAL SYMPTOMS TO DIAGNOSIS OR THERAPY INITIATION, ON DISEASE CONTROL AND MORTALITY, IN INFLAMMATORY MIOSITIS PATIENTS FROM THE INFLAMMATORY MIOSITIS REGISTRY FROM THE MADRID COMMUNITY (REMICAM). (June 2019) - Joven-Ibáñez, Beatriz; Nuño, Laura; López-Longo, Francisco J; Martinez-Barrio, Julia; Larena, Carmen; Maldonado, Valentina; Barbadillo, Carmen; Peña, Paloma García de la; Llorente, Irene; Muriel, Eva Tomero; Gómez, Ana Pérez; Moruno, Henry; et al.
Abstract : Background: In inflammatory diseases, such as rheumatoid arthritis, early treatment has demonstrated to improve disease control and decrease mortality. It is not known if an early treatment could have similar effects on inflammatory myositis (IM) patients. Objectives: To analyze if the delay between initial symptoms and diagnosis or therapy initiation influences disease control or mortality in IM patients. Methods: All patients from REMICAM were included (1). The influence of time elapsed between initial symptoms and diagnosis or start of therapy, and the year of diagnosis (before or after 2000), on mortality and disease control (defined as the possibility of glucocorticoid (GC) withdrawal due to IM improvement), was studied by means of survival analysis and regression proportional hazard bi and multivariate Cox models. All factors with p<0, 2 in bivariate were included in multivariate models. The mortality analysis was controlled for age, sex, and other known mortality factors: cardiovascular risk factors, interstitial lung diseases (ILD), cardiac involvement and cancer. The disease control analysis was controlled for age, sex and other known severity factors such as ILD, cardiac involvement and IM subtypes. Results: From 479 patients (74% females, 52% polimiositis, 44±22 years at diagnosis, 10±8 years follow up), 208 (43%) were diagnosed before 2000, and 473 (99%) received any treatment: 473 (99%) oral GC, 50/344 (15%) GC pulses, 78 (16%) HCL, 355 (74%) immunosuppressants (IS) (MTX 228, LF 10, AZA 190, CYP 44, MP 38, CyS 32), 55 (12%) biologics (RTX 45, abatacept 2, aTNF 16) and 79 (17%) IVIG. Disease control was more frequent in younger patients, diagnosed after year 2000, and was independently associated with less ILD presence, lower n° of therapies and a shorter time between the initial symptoms and the start of IS therapy (Table 1 ). Risk factors for mortality were age, male sex and cancer, but not the delay in diagnosis or in the start of therapy (Table 2 ) Conclusion: In the REMICAM cohort, disease control is more frequent in younger patients, diagnosed after 2000, with early initiation of IS therapy. Mortality was not associated with the delay in diagnosis or therapy in our study. Our data support the hypothesis that, in IM, as in other inflammatory diseases, an early treatment is essential to decrease inflammation and achieve disease control. Reference: [1] Nuño L, Rheumatol Clin 2017; 13:331-337 Disclosure of Interests: Beatriz Joven-Ibáñez Speakers bureau: Celgene, Novartis, MSD, Pfizer, AbbVie, and Janssen, Laura Nuño: None declared, Francisco J López-Longo: None declared, Julia Martinez-Barrio: None declared, Carmen Larena: None declared, Valentina Maldonado : None declared, Carmen Barbadillo: None declared, Paloma García de la Peña: None declared, Irene Llorente : None declared, Eva Tomero Muriel: None declared, Ana Pérez Gómez: None declared, Henry Moruno : None declared, Tatiana Cobo-Ibáñez: None declared, RAQUEL ALMODOVAR: None declared, LETICIA LOJO : None declared, María Jesús García de Yébenes: None declared, Patricia Carreira: None declared